Hybrid polymer composite materials : structure and chemistry - Thakur, Vijay Kumar; Thakur, Manju Kumari; Gupta, Raju Kumar, 1982- (Woodhead Publishing, 2017)
This book presents the latest on these composite materials that can best be described as materials that are comprised of synthetic polymers and biological/inorganic/organic derived constituents.
Keywords: polymery; polymerní kompozitní materiály; polymers; polymer composite materials; kolektivní monografie; collective monographs; elektronické knihy; electronic books